LA PEREQUAZIONE CATASTALE: UN MODELLO DI ANALISI - Monti, Bruno (GEOmedia, 2015)
This project provides the degree of quality class transfer cadastral citizen determined by the index of deviation between the actual class transfer with respect to the expected class transfer. The processing was performed on the entire building stock cadastral ordinary (category A0 * and * C0) composed of about 1.2 million urban housing units. Determining, for individual building urban index and relative offset value could return a model for analyzing massive and detail useful for defining the local tax policies and interventions aimed at achieving the fiscal equalization. Plays, therefore, particular interest is the geographical distribution of the index and the opportunity to represent the data for local areas diversified: the building, the building complex, the block, the neighborhood, the area of decentralization or areas chosen independently.